2016
DOI: 10.1002/bio.3150
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of luminescence efficiency of Dy3+ ions in strontium zinc phosphate glasses mixed with Pb3O4

Abstract: In this work we synthesized SrO-ZnO-P O glasses mixed with Pb O (heavy metal oxide) and doped with different amounts of Dy O (0.1 to 1.0 mol%). Subsequently their emission and decay characteristics were investigated as a function of Dy O concentration. The emission spectra exhibited three principal emission bands in the visible region corresponding to F → H (482 nm), H (574 nm) and H (663 nm) transitions. With increase in the concentration of Dy O (upto 0.8 mol%) a considerable increase in the intensity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The studies have revealed that, with the increase in rareearth content in the amorphous network, the spacing between the same decreases, which increases the magnitude of quenching in the properties due to ion clustering [3,[27][28][29][30]. Quenching occurs due to energy transfer between rare-earth ions in various network sites as the ion concentration increases.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The studies have revealed that, with the increase in rareearth content in the amorphous network, the spacing between the same decreases, which increases the magnitude of quenching in the properties due to ion clustering [3,[27][28][29][30]. Quenching occurs due to energy transfer between rare-earth ions in various network sites as the ion concentration increases.…”
Section: Physical Propertiesmentioning
confidence: 99%